2015
DOI: 10.1108/info-09-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the role of trust in cloud computing services

Abstract: Purpose – The purpose of this paper is to explain the role of trust in cloud computing services based on empirical evidence from interviewing executives of financial institutions in Ghana. The paper answers the questions: what is the role of trust in cloud computing service acquisition, and what policies promote trusted cloud computing services? Design/methodology/approach – This is an explanatory paper that is based on literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 32 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…The study has revealed that relatedness of users, integrity of users on the platform and competence of users are the key antecedents to privacy concerns on social media. In other words, perception of lack of integrity and low user competence have the tendency to lower the level of the trustworthiness of users [90]. Similarly, previous exposures and relationships can influence their trustworthiness.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has revealed that relatedness of users, integrity of users on the platform and competence of users are the key antecedents to privacy concerns on social media. In other words, perception of lack of integrity and low user competence have the tendency to lower the level of the trustworthiness of users [90]. Similarly, previous exposures and relationships can influence their trustworthiness.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This method is suitable for developing a complete understanding and a comprehensive view of the research domain and the Moreover, Hoffmann et al identified a cognitive coping mechanism that enables users to overcome or ignore privacy concerns and engage in online information self-disclosure [89]. Also the integrity and openness of social media platform can influence users' information disclosure behavior [90]. Trust of social media platforms is therefore predicated on integrity and openness.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study that aggregates these subjective individual perceptions of customers was deemed appropriate in order to acquire deeper understanding of factors that contribute to perception of data integrity (Alshamaila et al, 2013;Adjei, 2015). A longitudinal analysis of customers' perception of data integrity was conducted from January to December 2016.…”
Section: Methodsmentioning
confidence: 99%
“…A purposive sampling technique was used to select the informants because it offers the researcher to select respondents in a way that ensure extensiveness and diversity of individual customer perceptions. This sampling technique also reveals facts about the context such as social clues, opinions, attitudes, beliefs and feelings (Adjei, 2015;Yin, 2008). Gender, educational qualification or social exposure was not a metric considered in the sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation